2017
DOI: 10.1016/j.neuron.2017.06.038
|View full text |Cite
|
Sign up to set email alerts
|

Parallel Interdigitated Distributed Networks within the Individual Estimated by Intrinsic Functional Connectivity

Abstract: SummaryCertain organizational features of brain networks present in the individual are lost when central tendencies are examined in the group. Here we investigated the detailed network organization of four individuals each scanned 24 times using MRI. We discovered that the distributed network known as the default network is comprised of two separate networks possessing adjacent regions in eight or more cortical zones. A distinction between the networks is that one is coupled to the hippocampal formation while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

74
652
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 561 publications
(727 citation statements)
references
References 116 publications
74
652
1
Order By: Relevance
“…In this 17-network solution, the FPCN appears to be segregated into 2 distinct subsystems (see Yeo et al, Figure 9). Recent work suggests that a fractionation of the FPCN can be observed in the data of individual participants 13 . These findings represent important empirical evidence for functional heterogeneity within this network.…”
Section: Introductionmentioning
confidence: 99%
“…In this 17-network solution, the FPCN appears to be segregated into 2 distinct subsystems (see Yeo et al, Figure 9). Recent work suggests that a fractionation of the FPCN can be observed in the data of individual participants 13 . These findings represent important empirical evidence for functional heterogeneity within this network.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that the spatial extent of the DM network is variable among individuals (Braga & Buckner, 2017). To test whether the individual variability affected the distribution of the combinations of the connected networks, the regions that were likely to vary across individuals were excluded from analysis by removing the outermost vertices of the seven networks repeatedly until the resultant size of the networks was reduced to approximately one half of the original size (Figure 5b).…”
Section: Resultsmentioning
confidence: 99%
“…While four main subdivisions for the anterior cingulate cortex have been suggested as serving executive, cognitive, emotional and evaluative functions, extensive evidence of significant overlap between regions activated during pain, negative affect, and cognitive control points towards an integrated adaptive control hypothesis with the ACC involved to a large extent in aversively motivated action (Shackman et al, 2011). Essential to a function centered on comparing new with old content and doing this similarly for real compared to envisioned representations, distinguishable main networks have been found lately in human individuals, differing in their inclusion of hippocampal circuits and exhibiting interdigitated lay-outs in several cortical areas including neighbors of the ACC (Braga & Buckner 2017).…”
Section: Introductionmentioning
confidence: 99%